2008
DOI: 10.1902/jop.2008.070670
|View full text |Cite
|
Sign up to set email alerts
|

Early Wound Healing Following One‐Stage Dental Implant Placement With and Without Antibiotic Prophylaxis: A Pilot Study

Abstract: PICF content can be studied as early as 1 week following one-stage implant placement. The results raise doubts regarding the clinical usefulness of amoxicillin prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 46 publications
6
51
0
Order By: Relevance
“…The authors found low but measureable levels of proinflammatory cytokines in PICF after implant placement, which is consistent with previous data on inflammatory responses after implant placement 14,23,41 . Notably, the data of very low levels of IL‐8 and IL‐1α in PICF and GCF at the 1‐year follow‐up are in agreement with the findings of a previous report 34 showing low concentrations of IL‐1β in PICF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The authors found low but measureable levels of proinflammatory cytokines in PICF after implant placement, which is consistent with previous data on inflammatory responses after implant placement 14,23,41 . Notably, the data of very low levels of IL‐8 and IL‐1α in PICF and GCF at the 1‐year follow‐up are in agreement with the findings of a previous report 34 showing low concentrations of IL‐1β in PICF.…”
Section: Discussionsupporting
confidence: 90%
“…A previous report showed that after a 21‐day period of de novo plaque formation, GCF and PICF volumes were increased; 40 in a separate study, PICF volume was increased after implant placement 41 . These data indicate that GCF and PICF volumes are related to the level of inflammation in gingival and peri‐implant tissues, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…One study has further recommended a single post-operative dose as well [14]. The concept of prolonged antimicrobial therapy has been questioned [30,[32][33][34][35][36][37]. Out of our respondents, 96.1 % (n = 273) recommended continuing prolonged therapy in a range of 3-10 days after surgery, findings similar to the trend seen by Abukaraky et al [31] in their Jordanian sample.…”
Section: Discussionsupporting
confidence: 66%
“…Although this difference was not significant, it suggests that post‐surgical healing progressed more rapidly in the AZM group. The observed PICF volumes per 30‐second sample are comparable to those reported previously 26 , 28 . The data suggest that resolution of postoperative inflammation and healing of the junctional epithelium occurred more rapidly in the AZM group.…”
Section: Discussionsupporting
confidence: 89%